AGRIBUSINESS SEDAP MALAM FLOWER’S (POLIANTHES TUBEROSA L.) IN PASURUAN REGENCY: A STUDY OF PERCEIVED STRENGTHENING: AGRIBUSINESS SEDAP MALAM FLOWER’S (POLIANTHES TUBEROSA L.) IN PASURUAN REGENCY: A STUDY OF PERCEIVED STRENGTHENING - Hamidah Hendrarini; Wahyu Santoso (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2020)
Sedap Malam flowers (Polianthes tuberosa L.) are very popular behind the exotic market opportunities are still known to a variety of issues so need to explore the perceptions of business actors. The research objective is analyze the perceptions of farmers in the agribusiness Sedap Malam flowers and the policy of the Pasuruan Regency government in strengthening the agribusiness Sedap Malam flowers. The study was conducted in Rembang District, Pasuruan Regency with 55 farmers as respondents. The data analysis method uses a descriptive approach with the interpretation of the average value of the interval. The results of the study revealed that farmers' perceptions based on the conditions of land excretion put a statement Sedap Malam flowers (Polianthes tuberosa L.) cultivation with land that contains fertile clay and stipulating Sedap Malam flowers (Polianthes tuberosa L.) cultivation land did not conflict with the general spatial plan and regional layout of Pasuruan Regency were perceived better than other statements. Another interesting finding is that the understand technology places vegetative propagation of plants using tubers and determines the frequency and interface of fertilizer application based on crop needs, while farmers' perceptions of government policies on agribusiness Sedap Malam flower protecting of agricultural land for cultivation and pleasant Sedap Malam flowers (Polianthes tuberosa L.) as one of the regional icons, both are perceived very well to support the sustainability of farming. The policy support is a tangible form of strengthening that reflects the uniqueness of the region through its superior agriculture sector.